Tinjauan Yuridis terhadap Putusan Pengadilan Nomor 13/Pid.Sus-Anak/2017/PT.Pbr atas Sanksi Pidana terhadap Anak yang Menyimpan dan Menguasai Narkotika Jenis Shabu (Neolectura, 2023)
The aim of this study is to analyze and understand the criminal responsibility and safeguarding mechanisms for minors engaged in drug possession and control, as demonstrated by Court Decision Number: 13/Pid.Sus-Anak/2017/PT.Pbr. Normative juridical research methodology is applied, analyzing the interactions between relevant analyses and the relevant laws. The following is the formulation of the research problems: 1) How does the law govern the criminal penalties meted out to minors who use or possess drugs like Methamphetamine-type narcotics? and 2) According to Court Decision Number: 13/Pid.Sus-Anak/2017/PT.Pbr, what are the criminal penalties for kids who own and handle drugs like Methamphetamine-type narcotics? This research concludes, in the framework of the law, that isolating children when there are no other options has detrimental effects, including an ineffective rehabilitation process later on, particularly when the juvenile system and sanction system are applied to the children. The Juvenile Criminal Justice System (SPPA) and its implications, which call for the engagement of law enforcement in the resolution of juvenile cases, require special attention. The five pillars of sincere attempts to shield kids from drug abuse include providing legal protection and supervision for kids.